2022
DOI: 10.3390/tropicalmed7080166
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Scoping Review on Migrant Health Coverage in Thailand

Abstract: (1) Background: Thailand is a major migrant receiving country and pioneer of migrant health policy in the ASEAN region. However, on the ground, coverage of migrants is faced with multiple barriers. (2) Objectives: We aim to scope and analyse the types of available evidence on migrant health coverage in Thailand and identify knowledge gaps. Specifically, we characterise the literature along year of publication, migrant subpopulation, health domain, scope of coverage, methods, study design, objectives and result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Its UHC Service Coverage Index value reached 70 in 2021,8 which is relatively high among Association of Southeast Asian Nations (ASEAN) countries (after Singapore, Brunei and Thailand). Vietnam has also made significant progress towards achieving health equity 9 10. Researchers found that though there is a reduction of health inequity in most countries, inequity persists in some countries among ASEAN.…”
Section: Introductionmentioning
confidence: 99%
“…Its UHC Service Coverage Index value reached 70 in 2021,8 which is relatively high among Association of Southeast Asian Nations (ASEAN) countries (after Singapore, Brunei and Thailand). Vietnam has also made significant progress towards achieving health equity 9 10. Researchers found that though there is a reduction of health inequity in most countries, inequity persists in some countries among ASEAN.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, despite concerns regarding injuries to fishing boat workers, data are scarce with regard to assessment of occupational safety and health (OSH) conditions faced by these workers. The literature on migrant health in Thailand are generally broad with maternal and child health as the only notable area of focus [10], [20]. A previous study on Myanmar migrants who worked in seafood processing showed that nearly half of the participants reported musculoskeletal disorder, especially lower back pain [21], which may also be found among fishing boat crew members.…”
Section: Introductionmentioning
confidence: 99%
“…Significant problems among migrants are the spread of tuberculosis with a prevalence rate of 650 per 100,000 population, 3 sexually transmitted diseases (STDs), and malaria, 4 which have been stated to be a health alarm and epidemics among them and their dependents, as well as the recurring incidence of diseases. 5 Communicable disease, elephantiasis is about to disappear from Thailand, 6 yet due to migrants' working and living conditions, disease control is difficult. Thus, migrants' health became a considerable focus of the Thai government because safeguarding migrant health also protects the Thai economy and the right to health.…”
Section: Introductionmentioning
confidence: 99%